EVOLUTION OF THE MONGOL-OKHOTSK OCEAN AS CONSTRAINED BY NEW PALAEOMAGNETIC DATA FROM THE MONGOL-OKHOTSK SUTURE ZONE, SIBERIA - Kravchinsky V.A.; Cogné J.-P.; Harbert W.P.; Kuzmin M.I. (My University, 2002)
This paper presents new data from palaeomagnetic investigations on the Upper Palaeozoic and Mesozoic geological units from the Siberian platform and the Mongol–Okhotsk suture zone. Within the southern portion of the Mongol–Okhotsk suture we collected palaeomagnetic samples from the Late Permian Belektuy formation (Borzya region; 50.7°N, 116.9°E) and the Middle–Late Jurassic Shadaron formation (Unda-Daya; 51.5°N, 117.5°E). We sampled the Late Permian Alentuy formation (Khilok region; 50.8°N, 107.2°E), the Early to Middle Jurassic Irkutsk sedimentary basin (ISB; 52.0°N, 104.0°E), the Late Jurassic Badin formation (Mogzon region; 51.8°N, 112.0°E), and the Early Cretaceous Gusinoozesk formation (Gusinoe Lake region; 51.2°N, 106.5°E) additionally in the northern region of the Mongol–Okhotsk suture. Apart from the results of the ISB and Gusinoozersk formations, which show very large ellipses of confidence and might be the present-day geomagnetic field overprint, our results allow us to constrain the evolution of the Mongol–Okhotsk Ocean palaeomagnetically from the Late Permian to the Middle–Late Jurassic. They confirm that this large Permian ocean closed during the Jurassic, ending up in the late Jurassic or the beginning of the Cretaceous in the eastern end of the suture zone, as suspected on geological grounds. However, although geological data suggest a Middle Jurassic closure of the Mongol–Okhotsk Ocean in the west Trans-Baikal region, our data show evidence of a still large palaeolatitude difference between the Amuria and Siberia blocks. This is interpreted as a result of the quite fast closure of the ocean after the Middle Jurassic. Finally, our new palaeomagnetic results exhibit very large tectonic rotations around local vertical axes, which we interpret as probably arising both from collision processes and from a left-lateral shear movement along the suture zone, due to the eastward extrusion of Mongolia under the effect of the collision of India into Asia.